2014
DOI: 10.1097/aap.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Epidural and Peripheral Nerve Catheter Heating During Magnetic Resonance Imaging

Abstract: Background Many epidural and peripheral nerve catheters contain conducting wire that could heat during magnetic resonance imaging (MRI), requiring removal for scanning. Methods We tested 2 each of 6 brands of regional analgesia catheters (from Arrow International, B. Braun Medical, and Smiths Medical/Portex) for exposure to clinical 1.5 and 3 Tesla (T) MRI. Catheters testing as non-magnetic were placed in an epidural configuration in a standard human torso-sized phantom, and an MRI pulse sequence applied at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In 2002, Shellock reported that an epidural catheter manufactured with 604V stainless steel (Arrow International, Walpole, MA) showed limited deflection and rotation at 3T, but communication with Arrow indicates no catheters are currently manufactured using stainless steel. In the only other study found, Owens et al did not adhere to the strict testing standards published by ASTM International, and ISO/TS 10974 was not published at the time. Instead, the methodology focused on compliance with the FDA's RF and SAR guidelines under in vitro settings.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Shellock reported that an epidural catheter manufactured with 604V stainless steel (Arrow International, Walpole, MA) showed limited deflection and rotation at 3T, but communication with Arrow indicates no catheters are currently manufactured using stainless steel. In the only other study found, Owens et al did not adhere to the strict testing standards published by ASTM International, and ISO/TS 10974 was not published at the time. Instead, the methodology focused on compliance with the FDA's RF and SAR guidelines under in vitro settings.…”
Section: Discussionmentioning
confidence: 99%
“…Another point to be addressed in continuous EA with catheter insertion and MRI scan is the iatrogenic risk associated with MRI compatibility of the catheters [37]. In contrast to classical catheters made of nylon, which were used in this study, or polyether block amide, a number of new catheters are magnetic with coil-reinforcement, which can lead to significant catheter displacement under the magnetic field of an MRI scanner.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to classical catheters made of nylon, which were used in this study, or polyether block amide, a number of new catheters are magnetic with coil-reinforcement, which can lead to significant catheter displacement under the magnetic field of an MRI scanner. Furthermore, even if a few coil-reinforced catheters are not associated with magnetic displacement, hazardous temperature increases at the entry point may occur under a 3-T magnetic field [37]. This would cause a cutaneous burn at the catheter entry site and/or along the subcutaneous tunneling track.…”
Section: Discussionmentioning
confidence: 99%
“…CT has been recommended to locate retained catheters due to high resolution and ease of obtaining the test [7,8]. Magnetic resonance imaging (MRI) of the spine is not recommended as first diagnostic test of choice for ferromagnetic catheters due to metallic artifact, larger slice size, risk of neural injury secondary to heating of a wire-enforced catheter in the epidural space, and risk of catheter movement [9][10][11]. [1,3,7,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%